Edukasi Kesehatan Masyarakat Melalui Kegiatan Donor Darah Desa - Pramono, Didi; Fransiska, Junita Dwi; Lubna Askhiya , Siti; Pramudanti, Yolinda (Jurnal Bina Desa, 2025)
The purpose of this community service is to increase community awareness and involvement in blood donation. The community service approach applied is Participatory Rural Appraisal (PRA), which invites the community to get involved and participate. The method used is socialization and assistance for blood donors. The target community for the activity is the community of Ngemplak Village, Kudus. The activity was carried out on August 4, 2024 in collaboration with the Indonesian Red Cross. The results of the activity were that the community was very enthusiastic about participating in the socialization event and participating in donating their blood for humanity. A total of 30 villagers donated their blood, and the rest were unable to donate their blood for health reasons. The requirements for someone to be able to donate blood are a minimum age of 17 years, a maximum of 60 years, a minimum weight of 50 kg, physically and mentally healthy. not taking medication, not suffering from infectious diseases such as Hepatitis, Syphilis and others, for women not pregnant, breastfeeding, or menstruating, 2 hours before donating blood, eat first, get enough rest, sign the Informed Consent (Identity, medical history, and blood are examined and willing to be told the results).